The mediated learning experience and the mediator’s implications (2005)
It is clear that educators can affect learning positively or negatively, that a personal or professional attitude will immediately change the awareness pupils have toward our classes. Furthermore, as educators, we can not encourage in our pupils the development of good cognitive and socioemotional strategies if we do not constitute ourselves as a model to be followed. On account of these considerations, this article focuses on what Feuerstein (1986) has termed “mediation”, its conditions and the mediator’s profile. Thus, as language teachers, we have to think about the way we could improve and enrich the experience we are offering our pupils in order to make them feel and be intelligent cognitively and emotionally. Key words: Mediation, mediator, cognitive development, socioemotional development, intention, reciprocity, transcendence, meaning, competence, complexity, shared conduct, individuality, psychological difference, belonging, awareness Es claro que como educadores podemos afectar el aprendizaje de manera positiva o negativa y que una actitud personal o profesional podría cambiar de manera inmediata la disposición que tienen nuestros estudiantes hacia nuestra clase. Además, como educadores no podemos promover en nuestros educandos el desarrollo de estrategias cognitivas y socio-emocionales positivas si nosotros mismos no nos constituimos en un modelo digno de ser seguido. Teniendo en cuenta estas consideraciones, este artículo se enfoca en lo que Feuerstein (1986) llama “mediación”, sus condiciones y el perfil del mediador. Como profesores de idiomas debemos reflexionar acerca de las maneras como podríamos mejorar y enriquecer la experiencia que le estamos ofreciendo a nuestros estudiantes para que ellos se sientan y se hagan inteligentes tanto cognitiva como emocionalmente. Palabras claves: Mediación, mediador, desarrollo cognitivo, desarrollo socio-emocional, intencionalidad, reciprocidad, trascendencia, significado, competencia, complejidad, conducta compartida, individualidad, diferencia psicológica, pertenencia, disposición